Evaluation of Production Performance and Vibrio spp. Population Dynamics in Cantang Grouper at Different Stocking Densities in a Recirculating Aquaculture System (Advances in Tropical Biodiversity and Environmental Sciences, 2026)
Cantang grouper (Epinephelus fuscoguttatus × Epinephelus lanceolatus) is a hybrid fish with high economic value that is widely cultivated intensively using the Recirculating Aquaculture System (RAS). This study aims to (1) evaluate the production performance of cantang grouper at three levels of stocking density, (2) document the population dynamics of presumptive Vibrio spp., and (3) analyze the relationship between Vibrio spp. density and fish growth. The study used a 120-day comparative case study design with three stocking density treatments: 30 heads/m³ (Tank 1), 50 heads/m³ (Tank 2), and 70 heads/m³ (Tank 3). Production performance was evaluated based on specific growth rate and survival rate, while presumptive Vibrio spp. were determined using Thiosulfate Citrate Bile Salts Sucrose media. The relationship between Vibrio spp. density and SGR was analyzed using the Pearson correlation test. The results indicated that the best production performance was obtained at a stocking density of 30 heads/m³, while the lowest performance was observed at 70 heads/m³. The proportion of presumptive Vibrio spp. increases with stocking density, from 0.85% in Tank 1 to 2.15% in Tank 3. However, no significant association was found between presumptive Vibrio spp. density and decreased SGR (r = −0.185; p = 0.633; N = 9). Decreased production performance at high stocking density is thought to be related to space competition, physiological stress, and accumulation of toxic metabolites, although these mechanisms were not directly measured. Thus, stocking density is the main factor associated with the production performance of cantang grouper in the RAS system, while the increase in the population of presumptive Vibrio spp. plays a secondary role as an indicator of a decline in the quality of the cultivation environment
Keywords: Cantang grouper; Production performance; RAS; Stocking density; Vibrio spp.